Graphoplastic techniques as a fine psychomotor development tool for children 2 to 3 years old - Jiménez, Silvana; Del Pozo, Héctor; López Bravo, Oswaldo (Revista Universidad de Guayaquil, 2017)
The first three years of life in the child have been prioritized as part of a fundamental stage in the child's development. In the Integral Development Center "Mi Angelito Corre", it is necessary a plan to stimulate the child in his psychomotor development by means of graphoplastic techniques, besides working in an adequate leveling in the abilities and skills of the child. The study is aimed at determining if there is an incidence of fine psychomotor development and graphoplastic techniques in 3-yearold children. This study has a qualitative[1]correlational approach, which consists in the development of tests of psychomotor factors, fine language, social attitudes and gross motor skills by applying the Denver test. The information was entered and analyzed through the SPSS program. The statistic used to corroborate the proposed hypothesis is the Chi-square. It is concluded that, the application of graphoplastic techniques in the process of instruction of child preparation through activities that generate satisfaction and desire to learn and develop their skills. Finally, it was observed that some techniques were not pleasant to the child's perception and it was difficult to adapt to their stimulation.
Keywords: Psychomotor development; Development of thought; Plastic expression; Social skills; Graphoplastic techniques